Training to fatigue: The answer for standardization when assessing muscle hypertrophy? - Dankel, S. J.; Jessee, M. B.; Mattocks, K. T.; Mouser, J. G.; Counts, B. R.; Buckner, S. L.; Loenneke, J. P. (Sports Medicine, 2017)
Studies examining resistance training are of importance given that increasing or maintaining muscle mass aids in the prevention or attenuation of chronic disease. Within the literature, it is common practice to administer a set number of target repetitions to be completed by all individuals (i.e. 3 sets of 10) while setting the load relative to each individual`s predetermined strength level (usually a one-repetition maximum). This is done under the assumption that all individuals are receiving a similar stimulus upon completing the protocol, but this does not take into account individual variability with regard to how fatiguing the protocol actually is. Another limitation that exists within the current literature is the reporting of exercise volume in absolute or relative terms that are not truly replicable as they are both load-dependent and will differ based on the number of repetitions individuals can complete at a given relative load. Given that the level of fatigue caused by an exercise protocol is a good indicator of its hypertrophic potential, the most appropriate way to ensure all individuals are given a common stimulus is to prescribe exercise to volitional fatigue. While some authors commonly employ this practice, others still prescribe an arbitrary number of repetitions, which may lead to unfair comparisons between exercise protocols. The purpose of this opinion piece is to provide evidence for the need to standardize studies examining muscle hypertrophy. In our opinion, one way in which this can be accomplished is by prescribing all sets to volitional fatigue.